Initial performance of pineapple and utilization of rock phosphate applied in combination with organic compounds to leaf axils - Marihus Altoé Baldotto (Revista Ceres, 2011)
Rock phosphates have low solubility in water, but good solubility in acid. The use of organic compounds together with these phosphorus sources applied to the basal leaf axils of pineapple can increase the solubility of this phosfate source and increase the P availability to the crop. A greenhouse experiment was conducted using Araxá rock phosphate (10 g) in combination or not with solutions containing increasing concentrations of humic acids (0 to 40 mmol L-1 of carbon), with or without citric acid (0.005 mmol L-1), applied to basal leaf axils of pineapple cv. Pérola. Growth and nutritional characteristics of aerial plant parts were assessed. Growth rates of aerial parts and N, P, K, Ca and Mg contents increased curvilinearly with increasing concentration of carbon in the form of humic acids. Maximum values were found for the concentration of 9.3 mmol L-1 of carbon combined with 0.005 mmol L-1 of citric acid and natural phosphate.